What is food? researching a topic with many meanings - Gustafsson, Ulla (Sociological futures, 2020)
"This volume brings together contributions that provide a snapshot of current food research. What is food? acknowledges the many dimensions of food, including its social, cultural, symbolic and sensual qualities, while also being material in that it is fundamental to our survival. The contributions will be of interest to a wide range of students and researchers looking for a cutting-edge insight into how to frame and study food in areas related to the sociology of food, health, risk, poverty, sustainability and research methods"--